Semi-automated proof of supercongruences on partial sums of hypergeometric series. (July 2019) - Liu, Ji-Cai
Abstract: Using the software packageSigma developed by Schneider, we automatically discover and prove some combinatorial identities involving harmonic numbers, from which we deduce some supercongruences on partial sums of hypergeometric series. These results confirm some conjectural generalizations of van Hamme's supercongruences in some special cases, which were recently proposed byGuo (2017) .